2023
DOI: 10.1109/access.2023.3244741
|View full text |Cite
|
Sign up to set email alerts
|

Generative Adversarial Networks for Anomaly Detection in Biomedical Imaging: A Study on Seven Medical Image Datasets

Abstract: This study was part of a PhD dissertation supported by the Tehran University of Medical Sciences (TUMS) with the ethical code of IR.TUMS.SPH.REC.1399.060 from TUMS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 76 publications
0
2
0
Order By: Relevance
“…While GANs have shown promise, they also present challenges related to medical data, such as limited labeled samples and the complex nature of anomalies. In a similar vein, Esmaeili et al [2] investigate the use of GANs for anomaly detection in biomedical imaging. Their study, conducted on seven different medical imaging datasets, shows highly variable performance (AUC: 0.475-0.991; Sensitivity: 0.17-0.98; Specificity: 0.14-0.97), indicating the method's limitations and the need for further research.…”
Section: The Role Of Ai and ML In Anomaly Detectionmentioning
confidence: 99%
“…While GANs have shown promise, they also present challenges related to medical data, such as limited labeled samples and the complex nature of anomalies. In a similar vein, Esmaeili et al [2] investigate the use of GANs for anomaly detection in biomedical imaging. Their study, conducted on seven different medical imaging datasets, shows highly variable performance (AUC: 0.475-0.991; Sensitivity: 0.17-0.98; Specificity: 0.14-0.97), indicating the method's limitations and the need for further research.…”
Section: The Role Of Ai and ML In Anomaly Detectionmentioning
confidence: 99%
“…With the wide application of Generative Adversarial Networks (GAN) in image generation (Skandarani et al, 2023), these problems are expected to be solved. In recent years GAN has been widely used in medical image tasks such as image segmentation (Beji et al, 2023;Dash et al, 2023;Skandarani et al, 2023;Zhong et al, 2023), lesion classification (Chen et al, 2023;Fan et al, 2023), and lesion detection (Esmaeili et al, 2023;Vyas & Rajendran, 2023). And the study of GAN in medical image synthesis tasks has dominated.…”
Section: Introductionmentioning
confidence: 99%
“…Another benefit is that it should be able to detect any type of anomaly, potentially linked to different diseases. Deep generative models such as variational autoencoders (VAEs) (Kingma and Welling, 2013), generative adversarial networks (GANs) (Goodfellow et al, 2014) and more recently denoising diffusion probabilistic models (DDPMs) (Ho et al, 2020) have shown great results for image generation tasks and unsupervised anomaly detection (UAD) in medical imaging (Esmaeili et al, 2023), including neuroimaging Gong et al, 2023).…”
Section: Introductionmentioning
confidence: 99%